Large blade impeller application for turbulent liquid–liquid and solid–liquid mixing. (24th June 2022) - Montante, Giuseppina; Maluta, Francesco; Alberini, Federico; Iwasawa, Suzuka; Takenaka, Katsuhide; Paglianti, Alessandro
Abstract: Application of large blade impellers to turbulent single‐phase and two‐phase mixing is investigated in this work in order to provide a quantitative basis for estimating the possible advantages in industrial mixing operations with respect to fast impeller types. The analysis is based on the discussion of three‐dimensional velocity fields collected in a single‐phase vessel stirred by a Maxblend impeller by stereoscopic particle image velocimetry and of dispersed phase distribution and liquid mixing time obtained in solid–liquid and liquid–liquid systems by electrical resistance tomography. The results highlight that turbulent two‐phase mixing can be efficiently performed in baffled vessels stirred by large blade impellers both in shear‐rate controlled and bulk‐motion controlled processes.